Scleromyxedema: An atypical case - Emy Thomas; Anisha George; Divya Deodhar; Mary John (Wolters Kluwer Medknow Publications, 2015)
Scleromyxedema is a rare, chronic and persistent idiopathic disorder characterized by a generalized papular eruption due to dermal mucin deposition with an increase in dermal collagen. Patients usually have associated paraproteinemia. We describe the case of a 59-year-old gentleman with features of scleromyxedema, who had severe pruritus, scalp involvement, unrestricted mobility and associated peripheral eosinophilia, but no monoclonal gammopathy.